An iridium( iii / iv / v ) redox series featuring a terminal imido complex with triplet ground state - Kinauer, Markus; Diefenbach, Martin; Bamberger, Heiko; Demeshko, Serhiy; Reijerse, Edward J.; Volkmann, Christian; Würtele, Christian; van Slageren, Joris; de Bruin, Bas; Holthausen, Max C.; Schneider, Sven (Chemical science (Cambridge), 2018)
The iridium( iii / iv / v ) imido redox series [Ir(N t Bu){N(CHCHP t Bu 2 ) 2 }] 0/+/2+ was synthesized and examined spectroscopically, magnetically, crystallographically and computationally. The monocationic iridium( iv ) imide exhibits an electronic doublet ground state with considerable ‘imidyl’ character as a result of covalent Ir–N t Bu bonding. Reduction gives the neutral imide [Ir(N t Bu){N(CHCHP t Bu 2 ) 2 }] as the first example of an iridium complex with a triplet ground state. Its reactivity with respect to nitrene transfer to selected electrophiles (CO 2 ) and nucleophiles (PMe 3 ), respectively, is reported.